Effect of anti-biofilm peptide CRAMP-34 on the biofilms of Acinetobacter lwoffii derived from dairy cows - Liu, Lin; Li, Hui; Ma, Chengjun; Liu, Jingjing; Zhang, Yang; Xu, Dengfeng; Xiong, Jing; He, Yuzhang; Yang, Hongzao; Chen, Hongwei (Frontiers in Cellular and Infection Microbiology, 2024)
Dairy mastitis is one of the most common diseases in dairy farming, and the formation of pathogenic bacteria biofilms may be an important reason why traditional antibiotic therapy fails to resolve some cases of dairy mastitis. We isolated and identified three strains of A. lwoffii were with strong biofilm forming ability from dairy cow mastitis samples from Chongqing dairy farms in China. In order to investigate the effect of novel anti-biofilm peptide CRAMP-34 on A.lwoffii biofilms, the anti-biofilm effect was evaluated by crystal violet staining, biofilms viable bacteria counting and confocal laser scanning microscopy (CLSM). In addition, transcriptome sequencing analysis, qRT-PCR and phenotypic verification were used to explore the mechanism of its action. The results showed that CRAMP-34 had a dose-dependent eradicating effect on A. lwoffii biofilms. Transcriptome sequencing analysis showed that 36 differentially expressed genes (11 up-regulated and 25 down-regulated) were detected after the intervention with the sub-inhibitory concentration of CRAMP-34. These differentially expressed genes may be related to enzyme synthesis, fimbriae, iron uptake system, capsular polysaccharide and other virulence factors through the functional analysis of differential genes. The results of subsequent bacterial motility and adhesion tests showed that the motility of A.lwoffii were enhanced after the intervention of CRAMP-34, but there was no significant change in adhesion. It was speculated that CRAMP-34 may promote the dispersion of biofilm bacteria by enhancing the motility of biofilm bacteria, thereby achieving the effect of eradicating biofilms. Therefore, these results, along with our other previous findings, suggest that CRAMP-34 holds promise as a new biofilm eradicator and deserves further research and development.